The Association of Acute Motor Axonal Neuropathy (Guillain-Barre’ Syndrome Variant) with Coronavirus (SARS-Cov-2) in a Child: A Case Report - Nateghian, Alireza; Mohammadpour, Mozhde; Yousefi, Naseh; Khabbaz, Mohammad Sadegh; Moradi, Katayoun (Iranian Journal of Child Neurology, 2023)
Various reports of neurological manifestations of SARS-COV-2 infection after the virus outbreak are available, including anosmia, seizures, acute flaccid myelitis, Guillain-Barré syndrome (GBS), and encephalitis. Most of the literature has focused on the respiratory manifestation of SARS-CoV-2 infection in adults, but recent evidence showed that it is not confined to the respiratory tract. This report is about a rare variant of GBS acute motor axonal neuropathy (AMAN) in a child due to COVID-19 infection An 11 years old boy was referred to the hospital with a history of three-day lasting mild fever, and gastroenteritis, two weeks before starting symptoms. He was presented with progressive ascending weakness, paresthesia, and areflexia in four limbs four days ago. Nasopharyngeal swab polymerase chain reaction (PCR) was positive for SARS-CoV-2. The electrodiagnostic finding was compatible with acute generalized axonal motor neuropathy, and imaging revealed thoracolumbar syrinx and nerve root enhancement in lumbosacral MRI. Other lab tests were normal. GBS and its variant are one of the manifestations of SARS-CoV-2 in children. Children with an unexplained neurological process should be tested for SARS-CoV-2.